Pengaruh Pemupukan Nano Zinc dan Vitamin B1 terhadap Pertumbuhan Tanaman Alpukat YM (Persea americana) Menggunakan Sistem Irigasi Tetes - Deannisa Nirmala; Susiyanti Susiyanti; Abdul Hasyim Sodiq; Dewi Firnia (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
The avocado plants had various types and were favored by the Indonesian community. This was one of the reasons for the increased production. One type of avocado in Indonesia is the YM avocado from Lebak. The research aimed to enhance the growth of YM avocado plants by applying nano zinc fertilizer and vitamin B1. This research was carried out in May-August. It was an experimental study with a randomized block design with two factors. It employed Analysis of Variance (ANOVA) and post hoc tests using the Duncan Multiple Range Test (DMRT) at 5%. The first factor was Vitamin B1 (V) (15 mg/l, 30 mg/l, and 45 mg/l), the second factor was nano zinc fertilizer (Z) (2 ml/l, four ml/l, and six ml/l) and repeated three times, so there were 27 plants. Growth parameters observed included plant height, stem diameter, leaf length, leaf width, length-to-width ratio, leaf count, and leaf greenness index. The 45 mg/l dosages of vitamin B1 showed the best influence on planted growth, resulting in a height increase of 54.83 cm, a leaf length of 11.53 cm, a leaf length-to-width ratio of 2.57 cm, and a leaf greenness index of 50.11 units. The broadest leaf expansion occurred at the 15 mg/l dosage, reaching 5.44 cm. On the other hand, nano zinc fertilizer positively impacted stem diameter growth, especially with the optimal dosage of 6 ml/l, increasing from 8.50 mm. Combining nanozinc fertilizer and vitamin B1 supports plant growth by providing essential micronutrients and accelerating vegetative growth. However, vitamin B1 and nano zinc fertilizer do not exhibit a positive interaction in promoting the development of YM avocado plants.